The Effects of Aromatherapy with R.Damascena mill L. on Fatigue and Physical Discomfort of Operating Room Nurses - Meysam Hosseini Amiri; Nayyereh Raiesdana; Hanieh Bahadori (Mashhad University of Medical Sciences, 2024)
Background: Facing with emergencies in operating rooms can lead to nurses' fatigue and physical discomfort. The evidence shows that aromatherapy can effect on fatigue and physical discomfort.Aim: This study was performed with aim to investigate the effect of aromatherapy with R.Damascena essential oil on fatigue and physical discomfort in operating room nurses.Method: This randomized controlled clinical trial was conducted in 2023 on 60 operating room nurses in Qom University of Medical Sciences, Qom, Iran. Participants were divided into two equal intervention and control groups using the random blocking method. The intervention group received R.Damascena essential oil and the control group received normal saline as a placebo. In the intervention group, two drops of essence and in the control group, two drop of normal saline were applied to cotton ball, and the participants were asked to attach it to their clothes or scarf at a distance of ten centimeters below the chin and inhale it for 10 min. Fatigue and physical discomfort were assessed before and after aromatherapy.Results: After the intervention, the mean intensity of fatigue and physical discomfort significantly reduced with a mean decrease 18.38% (t=6.62, p<0.001) and 27.75% (t=5.19, p<0.001), respectively. There was significant difference between the intervention and control groups regarding fatigue (t=-2.78, p=0.007) and physical discomfort (t=-3.47, p=0.001).Implications for Practice: Aromatherapy with R.Damascena can reduce fatigue and physical discomfort in operating room nurses. Therefore, it is recommended to use aromatherapy along with other interventions to improve fatigue and physical discomfort.